Becoming John Curtin and James Scullin : Their early political careers and the making of the modern Labor Party. - Byrne, Liam (Melbourne University Publishing, 2020)
Before becoming the prime ministers who led Australia in moments of extraordinary crisis and transformation, John Curtin and James Scullin were two young working-class men who dreamt of changing their country for the better. Becoming John Curtin and James Scullin tells the tale of their intertwined early lives as both men became labour intellectuals and powerbrokers at the beginning of the twentieth century. It reveals the underappreciated role each man played in the events that defined the modern Australian Labor Party - its first experience of national government, the turmoil of war, the great conscription clash and party split of 1916, and the heated debates over the party's socialist objective. Becoming John Curtin and James Scullin shows how they became the leaders that history knows best by painting a portrait of two young men struggling to establish their identities and find their place in the world. It tells of their great friendships, loves and passions, and reminds us that these were real men, with real weaknesses, desires and dreams. It explains how their early political careers set the scene for their later prime ministerships as they honed the techniques of power that led them to the summit of Australian politics. This is the story of two young men striving to better the world they had inherited, a story of optimism and hope with enduring relevance for today's troubled politics.